2016
DOI: 10.3847/0004-637x/817/2/147
|View full text |Cite
|
Sign up to set email alerts
|

IMPLICATION OF FORMATION MECHANISMS OF HC5N IN TMC-1 AS STUDIED BY 13C ISOTOPIC FRACTIONATION

Abstract: We observed the J = 9−8 and 16−15 rotational transitions of the normal species and five 13 C isotopologues of HC 5 N to study its formation mechanisms toward the cyanopolyyne peak in Taurus Molecular Cloud-1, with the 45-m radio telescope of the Nobeyama Radio Observatory. We detected the five 13 C isotopologues with high signal-to-noise ratios between 12 and 20, as well as the normal species. The abundance ratios of the five 13 C isotopologues of HC 5 N are found to be 1.00:0

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 32 publications
(46 reference statements)
6
57
1
Order By: Relevance
“…For HC 7 N, our mean 12 C/ 13 C ratio is 103 ± 6, compared with the mean value of 94 ± 6 for HC 5 N (Taniguchi et al 2016) and 70 ± 5 for HC 3 N (Takano et al 1998). However, it should be noted that previous studies have found the ratio to be significantly smaller for the carbon atom in the CN end-group than for the other C atoms along the chain (Taniguchi et al 2016). Excluding the CN end-group, the mean ratios are 97 ± 7 for HC 5 N and 77 ± 7 for HC 3 N. Additional observations will be required to determine if this is also the case for HC 7 N.…”
Section: New Hc7n Isotopologuesmentioning
confidence: 93%
See 1 more Smart Citation
“…For HC 7 N, our mean 12 C/ 13 C ratio is 103 ± 6, compared with the mean value of 94 ± 6 for HC 5 N (Taniguchi et al 2016) and 70 ± 5 for HC 3 N (Takano et al 1998). However, it should be noted that previous studies have found the ratio to be significantly smaller for the carbon atom in the CN end-group than for the other C atoms along the chain (Taniguchi et al 2016). Excluding the CN end-group, the mean ratios are 97 ± 7 for HC 5 N and 77 ± 7 for HC 3 N. Additional observations will be required to determine if this is also the case for HC 7 N.…”
Section: New Hc7n Isotopologuesmentioning
confidence: 93%
“…Based on the relative similarities of the 12 C/ 13 C ratios in the different C atoms of HC 5 N in TMC-1, Taniguchi et al (2016) deduced that the main route to synthesizing the observed HC 5 N is via hydrocarbon ion (plus N-atom) chemistry. The trend for lower 13 C fractions in progressively larger cyanopolyynes is therefore indicative of a diminishing 13 C content in hydrocarbon ions of increasing size.…”
Section: New Hc7n Isotopologuesmentioning
confidence: 99%
“…Several observations to derive the 13 C isotopic fractionation of carbon-chain molecules have been carried out mainly at the cyanopolyyne peak in Taurus Molecular Cloud-1 (TMC-1 CP; d = 140 pc) in order to investigate their main formation pathways (HC 3 N (Takano et al 1998), HC 5 N (Taniguchi et al 2016a), CCS (Sakai et al 2007), CCH (Sakai et al 2010), C 3 S and C 4 H (Takano et al 1998). The authors suggested that the main formation pathway of HC 3 N in TMC-1 CP is the neutral-neutral reaction between C 2 H 2 and CN, based on the abundance ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that the main formation pathway of HC 3 N in TMC-1 CP is the neutral-neutral reaction between C 2 H 2 and CN, based on the abundance ratios. On the other hand, Taniguchi et al (2016a) proposed that the main formation mechanism of HC 5 N in TMC-1 CP is the ion-molecule reactions between hydrocarbon ions (C 5 H + m ) and nitrogen atoms followed by the electron recombination reactions, because significant differences in abundance among the five 13 C isotopologues of HC 5 N were not recognized. Recently, further confirmed the main formation mechanism of HC 5 N using the 14 N/ 15 N ratio of HC 5 N. The main formation pathways of HC 3 N were further investigated in the low-mass star-forming region L1527 (d = 140 pc) and the high-mass star-forming region G28.28-0.36 (d = 3 kpc) using the Nobeyama 45 m radio telescope (Taniguchi et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…There is a possibility that there is no significant differences in abundances among all of the 13 C isotopologus, when the main formation mechanism is the ion-molecule reactions (Taniguchi et al 2016). We also consider that scrambling may occur during the processes of these ion-molecule reactions.…”
Section: The Abundances Of Hmentioning
confidence: 99%